Oxacillin killing curve patterns of Staphylococcus aureus isolates by agar dilution plate count method. - Woolfrey, B F (1987)
The bactericidal dynamics of oxacillin against four Staphylococcus aureus isolates with known 24-h "persister" percentages were studied by using the agar dilution plate count method. Isolates were selected to provide a representative spectrum whose individual 24-h trough intrinsic persister percentages ranged from greater than 1 to less than 0.01%. Resultant agar dilution plate count method killing curve patterns were found to be reproducible and served to characterize each isolate. The paradoxical effect was observed for each isolate, with paradoxical peaks tending to develop and diminish sequentially during the course of oxacillin action. The observed strain-dependent dynamics of oxacillin killing underscore the artifactual nature of the so-called tolerance phenomenon and negate the usefulness of MBCs and MBC/MIC ratios for the characterization of S. aureus isolates.